A trajetória das mulheres ocidentais à vida pública - Coelho, Anna Ortiz Borges (2021)
This research aims to understand the historical trajectory of the inclusion of women in the public world. The time framework analyzed in this dissertation was the contemporary period, for it observed women's lives before Industrial Revolutions until today. One justifies the analysis of a long-standing historical period in order to identify changes in both the structure and the mentality of Western society, Brazilian society, in specific. To this end, one unravels, in the first chapter, the contemporary history of women in the Western world, to understand the social roles these women played and their slow historical evolution. In the second chapter, one studies the history of Brazilian women and their pursuit for equality, analyzing the differences between Brazilian history and the rest of the Western world. Finally, in the third chapter, one observes women's occupation in parliaments worldwide data and their representativeness. Therefore, one delimited the following countries as objects of a case study on their parliaments: United Kingdom, France, United States, Portugal, Argentina, and Brazil. This inclusion only can be for real, in the matter of equality, if women, more than having the right to paid work or the right to vote, have the assurance of effective political participation. What should mean: bringing demands of women to the spheres of the legislative, the executive and, the judiciary; and also changing the logic of social roles applied to men and women.